In vivo models of lung neutrophil activation. Comparison of mice and hamsters - Corteling, R.; Wyss, D.; Trifilieff, A. (2002)
BACKGROUND: Evidence suggests that both the migration and activation of neutrophils into the airway is of importance in pathological conditions such as pulmonary emphysema. In the present study, we describe in vivo models of lung neutrophil infiltration and activation in mice and hamsters. RESULTS: BALB/c and C57BL/6 mice were intranasally treated with lipopolysaccharide (0.3 mg/kg). Twenty-four hours after, animals were treated intranasally with N-Formyl-Met-Leu-Phe (0 to 5 mg/kg). Golden Syrian hamsters were treated intratracheally with 0.5 mg/kg of lipopolysaccharide. Twenty-four hours after, animals were treated intratracheally with 0.25 mg/kg of N-Formyl-Met-Leu-Phe. Both mice and hamster were sacrificed two hours after the N-Formyl-Met-Leu-Phe application. In both BALB/c and C57BL/6 mice, a neutrophil infiltration was observed after the sequential application of lipopolysaccharide and N-Formyl-Met-Leu-Phe. However, 5 times less neutrophil was found in C57BL/6 mice when compared to BALB/c mice. This was reflected in the neutrophil activation parameters measured (myeloperoxidase and elastase activities). Despite the presence of neutrophil and their activation status, no lung haemorrhage could be detected in both strains of mice. When compared with mice, the lung inflammation induced by the sequential application of lipopolysaccharide and N-Formyl-Met-Leu-Phe was much greater in the hamster. In parallel with this lung inflammation, a significant lung haemorrhage was also observed. CONCLUSIONS: Both mouse and hamster can be used for pharmacological studies of new drugs or other therapeutics agents that aimed to interfere with neutrophil activation. However, only the hamster model seems to be suitable for studying the haemorrhagic lung injury process